Strengthening Cultural Identity through Globalization of the Madurese Language in Syaikhona Kholil Religious Tourism, Bangkalan. - Siti Anuf; Zulkhaeriyah Zulkhaeriyah (Journal of Social, Culture, and Language, 2024)
This study aims to examine the strengthening of cultural identity through the globalization of the Madurese language in the context of Syaikhona Kholil religious tourism in Bangkalan. The background of this research is driven by the threat to local cultural identity due to the dominance of globalization, as well as the potential of religious tourism in improving the economic welfare of the community. This research uses a descriptive qualitative approach with the method of direct observation of religious rituals, interviews with local residents and tourists, as well as a comparative study of the use of Madurese language in other tourism sites. The results of the research are expected to strengthen the position of Madurese language as an important element in maintaining cultural identity in the era of globalization and contribute to the development of sustainable tourism in Madura. Keywords: Globalization, Madurese Language, Cultural Identity, Religious Tourism, Syaikhona Kholil